The evolution of Vietnamese industry - Nguyen Thi Tue Anh; Luu Minh Duc; Trinh Duc Chieu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The transfer from an import-substitution to an export-orientation strategy has been in effect in Vietnam since the reform process, Doi Moi, necessitating the reformulation of macroeconomic, trading and sectoral policies. As a result, the industry sector has experienced gradual growth as the country's economy is becoming more open and gaining deeper integration with regional and the world economies, as exemplified by membership in the ASEAN Free Trade Area (1995) and World Trade Organization (2006). To support this integration process, the structure of the industrial sector has been changed to more appropriate since the Doi Moi. Many export processing zones, industrial zones and economic zones have been set up to attract the interest of multi-sectors, including foreign and non-state investors. Consequently, the capacity, output and productivity of the industrial sector have improved considerably. But certain policy issues also arose during the industrial development process. These can be summarized into three main problems: minimal contribution from current policies to improving competitiveness, policy failure to encourage firm restructuring, and lack of a well-coordinated framework for industrial policy.
Keywords: L52; 330; industry; evolution; policy; productivity; Vietnam